Panel data analysis of factors of broadband services diffusion in OECD countries: Focus on deployment and migration - S. Shinohara; Y. Akematsu; M. Tsuji (International Telecommunications Society (ITS), 2011)
Deployment of broadband, particularly, FTTx, is now one of major policy objectives in many countries, including Japan, Korea, and the U.S., for example. The U.S. announced a National Broadband Plan which aimed at providing 100 million households with access to 100 Mbps broadband services by 2020. The purpose of this paper is to conduct an empirical analysis to identify factors affecting broadband service diffusion in OECD 30 member countries. In so doing, by considering the diffusion ratios of three broadband technologies, 30 countries are categorized into types, namely CATV (BB), DSL and FTTx. Then, the paper identifies the following factors which promote broadband services by an international comparison method: (1) initial conditions of Cable TV around year 2000; (2) open access obligations on copper subscriber lines; (3) relative connection speed of FTTx to DSL; and (4) business strategy of operators for investment in FTTx influence FTTx diffusion. (1) promotes CATV diffusion, (2) promotes DSL and FTTH, and (3) and (4) influence FTTH diffusion. Finally, the paper empirically verifies the above hypotheses and the migration process among three services using panel data model, which take care of the endogeneity problem using instrumental variable method. This analysis will provide an important basis for national broadband policy formulation in individual countries.
Keywords: L96; O33; O57; 330; OECD; broadband; FTTx; DSL; CATV; migration; unbundling; collocation; panel data analysis; instrumental variable method